One Body : An Essay in Christian Sexual Ethics - Pruss, Alexander R. (Book collections on Project MUSE., 2013)
This philosophical reflection on love and sexuality from a broadly Christian perspective is aimed at philosophers, theologians, and educated Christian readers. The author focuses on foundational questions on the nature of romantic love and on controversial questions in sexual ethics on the basis of the fundamental idea that romantic love pursues union of two persons as one body. The book begins with an account, inspired by St. Thomas Aquinas, of the general nature of love as constituted by components of goodwill, appreciation, and unitiveness. Different forms of love, such as parental, collegial, filial, friendly, fraternal, or romantic, the author argues, differ primarily not in terms of goodwill or appreciation but in terms of the kind of union that is sought. The author examines romantic love as distinguished from other kinds of love by a focus on a particular kind of union, a deep union as one body achieved through the joint biological striving of the sort involved in reproduction. Taking the account of the union that romantic love seeks as a foundation, the book considers the nature of marriage and applies its account to controversial ethical questions, such as the connection between love, sex, and commitment and the moral issues involving contraception, same-sex activity, and reproductive technology. With philosophical rigor and sophistication, the author provides carefully argued answers to controversial questions in Christian sexual ethics. -- Publisher's description.